IMPLEMENTATION OF BASIC FEASIBILITY AND FINANCIAL ANALYSIS OF FISH MEATBALL PRODUCTS PRODUCED BY SMALL AND MEDIUM-SIZED ENTERPRISES Y AND Z - Pratiwi, Elsy Aryanti; Soeprijadi, Liliek; Soeharso, Agusta Putri Balqis Linda; Panjaitan, Pola sabar tomohon; Siburian, Tina Franester; Napitupulu, Romauli Juliana (Proceedings of The Vocational Seminar on Marine & Inland Fisheries, 2026)
Basic eligibility in processing units is essential to ensure food safety and comply with PERMEN KP No. 17 of 2019, particularly for fishery product processing in micro and small enterprises (UMKM). Fish balls are one of the fishery products preferred by consumers due to their affordable price and good taste. The two UMKM observed use different raw materials, with UMKM Y using catfish (lele dumbo) and UMKM Z using swanggi fish. This study aims to identify the yield in the fish ball processing flow in both UMKM Y and Z, analyze gaps in the implementation of basic eligibility, and conduct financial analysis. The research involved surveys, direct observations, and interviews with UMKM owners, supported by yield calculations, evaluation of 19 basic eligibility clauses through gap analysis, and financial assessments including net profit, cost of goods sold (HPP), benefit–cost ratio (BCR), and break-even point (BEP) in units and rupiah. The production process follows SNI 7266:2017 with slight modifications according to UMKM conditions. The results show that UMKM Y has a yield of 106.5%, while UMKM Z has a yield of 120.2%. Gap analysis for SKP indicates that UMKM Y has an eligibility level of 47.49% with 0 critical, 3 serious, 2 major, and 4 minor findings, resulting in a C rating, meaning the UMKM cannot obtain SKP without corrective actions. UMKM Z has an eligibility level of 50.96% with 0 critical, 1 serious, 3 major, and 5 minor findings, resulting in a B rating, meaning the UMKM is still eligible to obtain SKP. Financial analysis for UMKM Y shows an investment cost of Rp15,246,000, total variable costs of Rp768,931, fixed costs of Rp2,174,600, total production costs of Rp2,943,531, gross revenue of Rp3,300,141, net income of Rp356,610, selling price of Rp22,000, HPP of Rp19,624, BCR of 1.1, BEP unit of 129, and BEP rupiah of Rp2,177,983. Meanwhile, UMKM Z shows an investment cost of Rp3,277,083, total variable costs of Rp6,586,027, fixed costs of Rp561,041, total production costs of Rp7,147,068, gross revenue of Rp11,520,000, net income of Rp4,372,932, selling price of Rp15,000, HPP of Rp9,306, BCR of 1.6, BEP unit of 1,112, and BEP rupiah of Rp16,687,207. The yield calculation results show that UMKM Y has a yield of 106.5%, while UMKM Z achieves 120.2%. The higher yield of UMKM Z has a direct impact on its business performance, as reflected by a more efficient total production cost relative to output, a lower cost of goods sold (COGS) of Rp9,306, and a higher net income of Rp4,372,932 with a BCR value of 1.6. In contrast, the lower yield of UMKM Y results in a smaller product output, leading to a higher COGS of Rp19,624, a lower net income of Rp356,610, and a BCR value of 1.1. This indicates that differences in yield significantly affect production efficiency and financial feasibility in each UMKM